An Observational Study of Constitutional Homoeopathic Remedies in Management of Cholelithiasis. (Homoeopathy for All, 2025)
Cholelithiasis is primarily consider  as a surgical disease by modern  medicine which can be readily  manageable and curable with  Homoeopathic medicine, as  Homoeopathy treats not only the  disease entity but also the patient  as a whole. With Homoeopathic  intervention surgery is not necessary  in Cholelithiasis and thus Gall  bladder was preserved and reverted  back to its normal functioning.  In the present study after giving  constitutional remedy to every  patient according to law of Similia  in Homoeopathy. The drugs were  given for the period of 3 to 5 month  as per need, the patient responded  well to our treatment and wonderful  results were found in recovery rate. It  proves the efficacy of constitutional  medicine in Cholelithiasis.
Keywords: Homoeopathy; Choleli thiasis; Constitutional remedy